Synthesis and photovoltaic performance of dibenzofulvene-based organic sensitizers for DSSC. Issue 38 (22nd September 2016) - Capodilupo, A.-L.; Giannuzzi, R.; Corrente, G.A.; De Marco, L.; Fabiano, E.; Cardone, A.; Gigli, G.; Ciccarella, G.
Abstract: Three novel 2D-π-A metal-free organic dyesTK 7 –9 containing a dibenzofulvene (DBF ) linked to two thiophene units as the π-bridge, diarylamines with and without alkoxy chains as donor groups and the cyanoacrylic acid moiety as the acceptor and anchoring group were synthesized. The new dyesTK were characterized by optical and electrochemical measurements and density functional theory calculations and were used as sensitizers in liquid dye-sensitized solar cells. The effects of alkoxy-functionalization of donor moiety and of hexyl chain insertion onto one thienyl ring of π-linker on dye properties and performances were investigated. The results discover the dyeTK7, bearing two simple diphenylamine groups without alkoxy chains, exhibits the best behavior in terms of light absorption and cell performance (PCE of 7.9% and photovoltaic parameters of J sc of 17.82 mA cm −2, V oc of 670 mV and FF of 0.66). Lower power conversion efficiencies of 6.3% and 6.1% were found forTK8 andTK9, respectively, as a consequence of the presence of the alkoxy chains. Graphical abstract: